2021
DOI: 10.3390/ijms222413267
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Studies of Blood and Vascular Wall in Atherosclerosis

Abstract: The review is devoted to the analysis of literature data related to the role of proteomic studies in the study of atherosclerotic cardiovascular diseases. Diagnosis of patients with atherosclerotic plaques before clinical manifestations is an arduous task. The review presents the results of research on the new proteomic potential biomarkers of coronary heart disease, coronary atherosclerosis, acute coronary syndrome, myocardial infarction, carotid artery atherosclerosis. Also, the analysis of literature data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 78 publications
(82 reference statements)
0
6
0
1
Order By: Relevance
“…Поиск и интеграция новых биомаркеров в существующие системы оценки ССР являются перспективным направлением персонализации кардиоваскулярной профилактики [21,22]. В настоящее время известно большое количество биомаркеров воспаления, имеющих потенциал для использования в исследованиях и клинической практике [23].…”
Section: Discussionunclassified
“…Поиск и интеграция новых биомаркеров в существующие системы оценки ССР являются перспективным направлением персонализации кардиоваскулярной профилактики [21,22]. В настоящее время известно большое количество биомаркеров воспаления, имеющих потенциал для использования в исследованиях и клинической практике [23].…”
Section: Discussionunclassified
“…Identifying proteins linked to specific atherogenicmechanisms sheds light onto the molecular pathophysiology of cardiometabolic disturbances. Although there have been multiple studies that found highly expressed proteins within atherosclerotic tissue, only a small number of these findings was replicated when using blood samples [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This type of workflow implemented with low-invasiveness samples may be an ideal option to be applied in screening and diagnostic programs with the aim of identifying new pharmacological targets and potential biomarkers, as well as improving the tumor clinical management. In the field of cardiovascular biomedicine, the deployment of proteomic approaches is mainly focused on the discovery of circulating protein biomarkers of heart diseases and the elucidation of disease-associated mechanisms and potential therapeutic targets in cardiovascular tissues [ 7 , 8 ]. Nav1.5 protein corresponds to the sodium channel protein type 5 subunit alpha (SCN5A) of the human cardiac voltage-gated sodium channel.…”
mentioning
confidence: 99%